Jurnal Sastra Indonesia: Indonesia - Angger Rusmawati; Lutfi Syauki Faznur (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2020)
Writing the following research will raise the theme of the principles of politeness contained in a drama script. The data source for this study was obtained from a drama entitled